EXPLORING SENSE OF PLACE FOR THE SUSTAINABILITY OF HERITAGE DISTRICT IN YOGYAKARTA - Emmelia Tricia Herliana; Himasari Hanan; Hanson Endra Kusuma (Journal of Architecture&ENVIRONMENT, 2017)
Yogyakarta is well-known as a historical city and the centre of Javanese culture that attracts many tourists to come. In recent year, Yogyakarta has been very popular to domestic and international tourists in that many heritage places in the city have been developed to distinctive tourist destinations, yet no reasonable criteria has been developed to guide its development. This study assumed that places with distinctive identity or character or uniqueness are the most interested object of attraction for tourists. Therefore, the study will explore the sense of place as the important success factor in sustaining a heritage place as tourist attraction and identify aspects of a place that might contribute to its sustainability. Two heritage districts: Kotagede and Kotabaru are selected for evaluating aspects of place that are significantly contributing to the historical and cultural image of the city of Yogyakarta. The study identify and analyze the existing condition of physical attributes, performed activities and conception of the place. Indicators being used are developed from the current research undertaken by geographer and environmental psychologist. The study resulted to the conclusion that an interconnection of many aspects rather than identity of the place is the critical factor for the sustainability of a heritage place.